PENINGKATAN MUTU PRODUK IKAN TONGKOL ASAP MELALUI SOSIALISASI TEKNIK PENGEMASAN PADA POKLASHAR MARNIATI DI WILAYAH DESA TRITIRO - Yasnidar, Yasnidar; Hasan, Tahirah; Helena, Shifa; Warsidah, Warsidah; Nurdiansyah, Syarif Irwan (Program Studi Ilmu Kelautan, FMIPA Universitas Tanjungp, 2023)
Smoked cob fish is one of the processed marine fisheries commodities which is much loved by the community, both local people and outside the Tritiro village area. The marketing of this smoked fish product reaches outside the Tritiro village area, which causes the need for packaging that can maintain the quality of the fish until it reaches the customer. This independent community service activity (PKM) aims to improve the quality of smoked fish products produced by smoked fish processing groups through socialization of packaging techniques using a vacuum sealer so as to extend the shelf life of smoked fish, especially in distribution outside the region. The activity was attended by smoked fish processor Poklashar Marniati in the South Kalumpang sub-village, with lecture and practice methods or demonstrations in using a vacuum sealer. The results of the activity show that packaging with a vacuum sealer can increase the durability of smoked tuna so that the risk of damage when shipping out of the area can be minimized. Monitoring and evaluation of packaging socialization activities with this technique is carried out during the PKM activity and up to 3 months after the completion of the activity. The monitoring and evaluation results show that this packaging socialization can increase the productivity of processed smoked fish in the village.Keywords : smoking, vacuum, sealer, smoked cob fish, Tritiro village